1995
DOI: 10.1111/j.1399-6576.1995.tb04143.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide is a potent cerebrovasodilator in humans when added to isoflurane. A transcranial Doppler study

Abstract: Nitrous oxide during neurosurgical procedures is almost always given in combination with either volatile or intravenous anesthetics. The modifying influence of such interventions has been studied clinically and in experimental settings; the reported findings, however, are inconsistent. The present study compares the cerebrovascular effects of MAC equivalent concentrations of isoflurane alone and isoflurane plus nitrous oxide. Twenty lumbar laminectomy patients randomized either to receive isoflurane or isoflur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In another study involving direct stimulation of the stellate ganglion during surgery, CFV increased possibly due to a vasoconstriction at the MCA (40). However, patients in that study were anaesthetized both with isoflurane, which is known to ablate autoregulation (37), and with nitrous oxide, which is a potent vasodilator when combined with isoflurane (36). Therefore, the increases in CFV during stellate ganglion stimulation were likely the result of increased mean BP augmenting CFV through vessels with impaired autoregulation.…”
Section: Discussionmentioning
confidence: 87%
“…In another study involving direct stimulation of the stellate ganglion during surgery, CFV increased possibly due to a vasoconstriction at the MCA (40). However, patients in that study were anaesthetized both with isoflurane, which is known to ablate autoregulation (37), and with nitrous oxide, which is a potent vasodilator when combined with isoflurane (36). Therefore, the increases in CFV during stellate ganglion stimulation were likely the result of increased mean BP augmenting CFV through vessels with impaired autoregulation.…”
Section: Discussionmentioning
confidence: 87%
“…It is generally accepted that inhalational anesthetic agents have been shown to produce dose-dependent dilation in cerebral vessels and increase in CBF (Matta et al, 1999;Strebel et al, 1995), but its reported effects on rCBF are often contradictory depending on the condition of material or patients, and the huge variety of methods and techniques in both anesthesia and CBF evaluation.…”
Section: Discussion Rcbf and Anestheticsmentioning
confidence: 99%
“…28 Stimulation of T 2 and T 3 sympathetic ganglia during surgery caused marked increases in CFV, 29 which could have been due to vasoconstriction at the vessel of insonation or increases in CBF. Concurrent increases in MAP during stimulation may have augmented CBF through vessels with impaired autoregulation secondary to anesthetic effects on cerebrovascular control, 30,31 resulting in increased CBF and CFV. Direct infusions of norepinephrine in both anesthetized 32 and conscious 33 patients have not affected CFV, but cerebral vascular resistance was increased, possibly because of the myogenic constriction after the increase in systemic MAP.…”
Section: Discussionmentioning
confidence: 99%